In the Beginning was the deed? Discovering the presence of the spirit in social construction (2018)
The relationship between socio-constructionism and Christian theology has not been sufficiently explored. This paper critically analyses some of the main insights of socio-constructionist theories and suggests that a reinterpretation of the idea of social construction from a theistic perspective can avoid the unresolved problems of its radical versions. The paper argues that an order of meaning, whose origin cannot be reduced to human action, has to be presupposed for practices of social construction to work. This resonates with the belief in God's action in human reality. © 2018 Nicolaus Copernicus University. All rights reserved.